The Rehabilitation Landscape in a Low-to-Middle-Income Country: Stakeholder Perspectives and Policy Implications-A Qualitative Study - Rentia Amelia Maart PhD; Gubela Mji PhD; Linzette Deidré Morris PhD; Dawn Verna Ernstzen PhD (SAGE Publishing, 2024)
The need for rehabilitation is increasing on a global level due to a rise in non-communicable diseases, aging and medical advances, and in South Africa (SA), due to the quadruple burden of disease. More information is required regarding rehabilitation scope and practices in SA to optimize the provision of rehabilitation interventions in the context of the transforming health care sector in SA, a low-to-middle-income country (LMIC). The purpose of this study is to explore the perspectives of South African rehabilitation stakeholders on the landscape of rehabilitation in SA. A descriptive qualitative study, with an interpretive approach, was used to explore stakeholder perspectives on rehabilitation practices in the public health care sector of SA. Semi-structured interviews were conducted with 12 rehabilitation stakeholders. Data were analyzed using a combination of deductive and inductive processes to generate themes and categories. We identified 5 main themes, with subsequent categories and sub-categories. The themes include a composite definition of rehabilitation, core elements of rehabilitation provision, challenges affecting rehabilitation practices, the importance of policy implementation, and the progress of rehabilitation in SA. Despite a common understanding of rehabilitation practices in SA amongst stakeholders, many persistent challenges hamper the delivery of effective rehabilitation services. We recommend that further research explore the rehabilitation needs of end-users, together with collaborative research for priority setting on the translation of policy to practice ensuring equitable and quality rehabilitation service delivery.